Pemahaman QS. at-Takatsur: Analisa Kritis Pandangan Pendidikan Agama Islam terhadap Fenomena Flexing - Aslihah Aslihah; Wasehudin Wasehudin; Abdul Muin; Susari Susari (Jurnal Semiotika Quran, 2024)
This article discusses the view of Islamic Religious Education towards the phenomenon of flexing or showing off wealth in QS. at-Takatsur. Using a qualitative descriptive-analitycly method, this article concludes that QS. at-Takatsur strongly criticizes human behavior that is too attached to materialistic world competition and excessive wealth. The verses of surah at-Takatsur warn of the negative consequences  of unbalanced  flexing. The emphasis  on  the importance of simplicity, gratitude, and justice in the management of wealth is the basis for the view of Islamic Religious Education towards flexing behavior. Thus, the view of Islamic Religious Education towards flexing as a challenge can be overcome through a deep understanding of the teachings of the Qur'an, the implementation of Islamic values in everyday life, and joint efforts to form a more balanced and just society. This article is expected to be one of the references and a better understanding of Islamic values that can shape Islamic character and reduce the negative impact of the flexing phenomenon in society.